SISTEM EKONOMI DUNIA - Maryam Batubara; Tria Rizki Maulia; Rizkie Ragilita; M. Harry Pranata; M. Iqbal Suharno (CV. KAMPUS AKADEMIK PUBLISING, 2023)
. In the world economy there are four systems, namely capitalist, communist, welfare state and Islamic economic systems where the distribution of wealth is based on the Al-Qur'an and Hadith. Scientific studies on Islamic economics and finance have emerged and experienced development since the 1970s, both in the Middle East and in other Islamic countries. Since then, the Islamic economic system has emerged as a discourse and is seen as an alternative choice.